PC.94 Teaching the teachers: The hidden public health impact of preterm birth. (9th June 2014) - Johnson, S; Gallimore, I; Gilmore, C; Jaekel, J; Strauss, V; Wolke, D
Abstract : Background: Children born preterm are at high risk for adverse cognitive and behavioural outcomes. Teachers are increasingly responsible for identifying problems and providing long-term support, yet no studies have assessed how prepared they feel to meet the needs of these children. Methods: A 33-item scale to assess knowledge of the outcomes and educational needs of preterm children was developed and validated and appended with questions to assess demographic characteristics and information needs. Emails were sent to head teachers of all schools in England inviting staff to complete this questionnaire online. Results: Responses were obtained from 734 teachers (64% community schools; 25% academies; 11% independent schools) ranging from Early Years to Further Education teachers. The proportion of teachers' correct answers on the knowledge scale ranged from 0% to 87% with a mean of 44.5% (SD 16.9) correct. Teachers' poorest knowledge related to mathematics, developmental delay, attention and social skills. Only 14% felt they had received sufficient training about preterm birth and only 39% felt adequately equipped; 84% of teachers requested training about preterm birth. Conclusions: Three children in an average class size will be born preterm, yet teachers lack knowledge of their outcomes and educational needs and most feel ill equipped to support them in school. Worryingly, their areas of poorest knowledge related to the most common adverse outcomes following preterm birth. There is a pressing need for clinicians to 'teach the teachers' about preterm birth to reduce the public health impact of this growing population of children.